Emerging West African Genotype Chikungunya Virus in Mosquito Virome - Pengpeng Xiao; Yujia Hao; Yuge Yuan; Wenzhou Ma; Yiquan Li; He Zhang; Nan Li (Virulence)
We studied the viromes of three dominant mosquito species in Wenzhou, a coastal city in Zhejiang Province, using metavirome sequencing, with 18 viral families identified. Viral sequences were verified by RT-PCR. The JEV E gene was most closely related to the 1988 Korean strain. DENV sequences were most closely related to the 1997 Australian strain. CHIKV-E1-1 was most closely related to the 1983 Senegal strain and belonged to West African genotype CHIKV. Remarkably, this is the first time that a West African genotype of CHIKV has been detected in Zhejiang Province. Mutations in the CHIKV-E1-1 protein A226V may increase infectivity in Ae. albopictus. Three non-conservative mutations of CHIKV-E1-1 (D45H, D70H and V290D) may have an impact on the function. In conclusion, our study reveals the diversity of mosquito-borne viruses and potential emerging outbreaks in the southeast coastal region of China, providing new perspectives for mining the ecological characterization of other important arboviruses.